2021
DOI: 10.21037/jtd-21-1153
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between pre-procedural elevated arterial lactate and contrast-induced nephropathy following primary percutaneous coronary intervention

Abstract: Background: Risk stratification has been one of the main steps in preventing contrast-induced nephropathy (CIN), which is a common complication after percutaneous coronary intervention (PCI). Elevated arterial lactate is a biomarker indicating severe disease condition and post-intervention complications. The relationship between lactate and CIN has not been established. This study is performed to investigate the relationship between elevated arterial lactate level and contrast-induced nephropathy (CIN). Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Arterial lactate was recently introduced as a parameter in the CRATE score for AKI prediction among patients who underwent cardiac surgery ( 13 ). Moreover, Yang et al ( 22 ) found that lactate level performance in predicting CIN among patients with STEMI following PPCI was similar to that of the MRS, a widely used and externally validated model ( 2 , 23 ). However, data regarding the additional value of lactate parameters in MRS for AKI prediction among such patients is lacking.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Arterial lactate was recently introduced as a parameter in the CRATE score for AKI prediction among patients who underwent cardiac surgery ( 13 ). Moreover, Yang et al ( 22 ) found that lactate level performance in predicting CIN among patients with STEMI following PPCI was similar to that of the MRS, a widely used and externally validated model ( 2 , 23 ). However, data regarding the additional value of lactate parameters in MRS for AKI prediction among such patients is lacking.…”
Section: Discussionmentioning
confidence: 85%
“…Yan et al ( 21 ) analyzed 280 patients with AMI who underwent emergency PCI and demonstrated that high lactate levels at baseline were associated with an increased risk of contrast-induced AKI. A previous study that evaluated 227 patients with STEMI revealed that a pre-procedural arterial lactate level of ≥ 2.0 mmol/L was a predictive factor of CIN ( 22 ). However, both studies were limited by their small sample sizes and they only investigated the predictive value of baseline lactate levels.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, serum lactate is an indicator of disease severity. Previous reports indicate that baseline high lactate levels are associated with an increased risk of contrast-induced acute kidney injury and poor cardiorenal outcomes in acute myocardial infarction patients undergoing emergency PCI [12][13][14][15]. So far, research establishing whether the relationship between hyperuricemia and AKI in STEMI patients is modified by lactate remains unpublished.…”
Section: Introductionmentioning
confidence: 99%